Calculating Zeros of the -Genocchi Polynomials Associated with -Adic -Integral on - C. S. Ryoo (International Journal of Mathematics and Mathematical Sciences)
In this paper we construct the new analogues of Genocchi the numbers and polynomials. We also observe the behavior of complex roots of the -Genocchi polynomials , using numerical investigation. By means of numerical experiments, we demonstrate a remarkably regular structure of the complex roots of the -Genocchi polynomials . Finally, we give a table for the solutions of the -Genocchi polynomials .